Handbook of research on recent perspectives on management, international trade, and logistics - Koç Aytekin, Güner, 1969-; Dogru, Caglar, 1983- (Advances in logistics, operations, and management science (ALOMS) book series., 2021)
"This book presents the effective management of the supply chain, including especially the latest trends as, supply chain modeling, e-business solutions, and digitalizing the supply chain process by revealing the latest data based on research on the issues of entrepreneurship, innovation, contemporary management techniques, and global supply chain management"--